Aging biological markers in a cohort of antipsychotic-naïve first-episode psychosis patients. (October 2021) - Talarico, Fernanda; Xavier, Gabriela; Ota, Vanessa Kiyomi; Spindola, Leticia M.; Maurya, Pawan Kumar; Tempaku, Priscila Farias; Moretti, Patrícia S.; Gadelha, Ary; Noto, Mariane; Noto, Cristiano; Cordeiro, Quirino; Bressan, Rodrigo A.; et al.
Abstract: Schizophrenia is a severe and multifactorial disorder with an unknown causative pathophysiology. Abnormalities in neurodevelopmental and aging processes have been reported. Relative telomere length (RTL) and DNA methylation age (DMA), well-known biomarkers for estimating biological age, are both commonly altered in patients with schizophrenia compared to healthy controls. However, few studies investigated these aging biomarkers in first-episode psychosis (FEP) and in antipsychotic-naïve patients. To cover the existing gap regarding DMA and RTL in FEP and antipsychotic treatment, we aimed to verify whether those aging markers could be associated with psychosis and treatment response. Thus, we evaluated these measures in the blood of FEP antipsychotic-naïve patients and healthy controls (HC), as well as the response to antipsychotics after 10 weeks of treatment with risperidone. RTL was measured in 392 subjects, being 80 FEP and 312 HC using qPCR, while DMA was analyzed in a subset of 60 HC, 60 FEP patients (antipsychotic-naïve) and 59 FEP-10W (after treatment) using the "Multi-tissue Predictor"and the Infinium HumanMethylation450 BeadChip Kit. We observed diminished DMA and longer RTL in FEP patients before treatment compared to healthy controls, indicating a decelerated aging process in those patients. We found no statistical difference between responder and non-responder patients at baseline for both markers. An increased DMA was observed in patients after 10 weeks of treatment, however, after adjusting for blood cell composition, no significant association remained. Our findings indicate a decelerated aging process in the early phases of the disease. Highlights: Relative telomere length (RTL) and DNA methylation age (DMA) are well known biomarkers for estimating biological age. Antipsychotic-naïve FEP patients presented diminished DMA and longer RTL compared to healthy controls. Diminished DMA and longer RTL indicates a decelerated aging process on drug-naïve FEP patients. Accelerated aging (observed in schizophrenia) might be related to the treatment and not to pathophysiology of the disease.